Картографічне забезпечення розвитку туризму і рекреації - Ковальчук, Іван; Kovalchuk, Ivan (Видавництво Львівської політехніки, 2019)
Важливою складовою забезпечення їх розвитку є картографічна продукція туристично-рекреаційної тематики – атласи, топографічні і тематичні карти, плани туристських об’єктів (пам’яток природи, історії, культури тощо) та населених пунктів, 3-D моделі атрактивних утворень, туристські інтерактивні інтернет-карти тощо. Розглядаються питання класифікації складових картографічного забезпечення туризму, створення нових його видів, вибору масштабу туристських карт різного призначення.

In the conditions of informatization in all spheres of activities, that are vital for society, a major role is delegated to the creation of the corresponding mapping support. Each branch of the economy requires specialized information and analytical products that reflect the properties of the environment in which the economic objects are created and being operated, influencing factors, risks and prospects of development. Tourism and recreation industry is no exception. An important component of ensuring their development is the cartographic products of tourist and recreational themes - atlases, topographical and thematic maps, plans of tourist objects (monuments of nature, history, culture etc.) and settlements, 3-D models of attractional formations, tourist interactive web-maps etc. The questions of components classification in the process of cartographic support of tourism, creation of new types of it, the choice of scale for tourist maps of various purposes and other topical issues of tourist cartography are considered in the paper.
Cartographic support for the development of tourism and recreation
Keywords: геоінформаційна система; інформаційна база туризму; рекреація; картографічне забезпечення розвитку туризму; GIS; information base of tourism; recreation; cartographic support for tourism development; 528.94